2011
DOI: 10.1371/journal.pone.0018591
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Intensity Causes Perceived Changes in Arousal Levels in Music: An Experimental Investigation

Abstract: Listener perceptions of changes in the arousal expressed by classical music have been found to correlate with changes in sound intensity/loudness over time. This study manipulated the intensity profiles of different pieces of music in order to test the causal nature of this relationship. Listeners (N = 38) continuously rated their perceptions of the arousal expressed by each piece. An extract from Dvorak's Slavonic Dance Opus 46 No 1 was used to create a variant in which the direction of change in intensity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 27 publications
6
67
1
2
Order By: Relevance
“…For example, we have recently presented evidence that the perception of loudness in a well-studied Dvorak Slavonic Dance is driven mainly 'bottom-up', bearing a very high correlation with intensity almost throughout the studied extract (Ferguson, Schubert, & Dean, 2011). Correspondingly we have been able to demonstrate by experimental manipulations of intensity profiles that in this particular piece, and in three other stylistic diverse pieces, intensity can be a major driver of perception of change and expressed arousal (Dean, Bailes, & Schubert, 2011). In the same paper we also showed that intensity might have actions in addition to those mediated via perceived loudness, a matter for future investigation.…”
Section: Computational Cognitive Modelling and Its Potential Applicatsupporting
confidence: 64%
“…For example, we have recently presented evidence that the perception of loudness in a well-studied Dvorak Slavonic Dance is driven mainly 'bottom-up', bearing a very high correlation with intensity almost throughout the studied extract (Ferguson, Schubert, & Dean, 2011). Correspondingly we have been able to demonstrate by experimental manipulations of intensity profiles that in this particular piece, and in three other stylistic diverse pieces, intensity can be a major driver of perception of change and expressed arousal (Dean, Bailes, & Schubert, 2011). In the same paper we also showed that intensity might have actions in addition to those mediated via perceived loudness, a matter for future investigation.…”
Section: Computational Cognitive Modelling and Its Potential Applicatsupporting
confidence: 64%
“…To further assess mechanistic causalities, intervention experiments are called for, such as those that we earlier undertook successfully in relation to the influence of acoustic intensity change profiles upon the continuous perception of affect (Dean, Bailes, & Schubert, 2011). The time series analysis approach is one way to reach a level of understanding of the complex temporal relationships that can guide such intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity changes also substantially drive perception of affect in most pieces, and we showed with an empirical intervention that changing the intensity profile of certain pieces could correspondingly change the perception of their expressed arousal (Dean, Bailes, & Schubert, 2011).…”
mentioning
confidence: 81%
“…For valence, even intensity was no longer required in the optimal model, but its degree of fit remained poor, and this observation is not powerful. The result suggests that indeed event density may well be influential particularly on the perception of arousal, and that this hypothesis will bear further investigation by means of experimental perturbation studies manipulating event density, such as we have previously conducted with acoustic intensity (Dean et al, 2011). In the case of event density, such experiments will require specially generated stimuli, or substantial segment by segment speeding and slowing of audio stimuli.…”
Section: Analyzing the Impact Of Agency: Dissecting Perceived Change mentioning
confidence: 93%
See 1 more Smart Citation